CYTOTOXIC, ANTIMICROBIAL AND ANTIVIRAL EVALUATION OF THE AERIAL PARTS OF SORGHUMVIRGATUMHACK - Atef A. El-Hela1,⃰Ismail A.Hussein1, EhabM. Mostafa1, 3, Mohammed M. Ghoneim1, 2 (Journal of Biomedical and Pharmaceutical Research, 2017)
Sorghum virgatum (Hack) belongs to Poaceae (Graminae) family, which represented in flora of Egypt by four species. It worth noting that nothing was reported about phytochemical and biological investigation of S.virgatum. Therefore, phytochemical and biological investigation of the different extracts of S. virgatumisimportant. Sorghum is rich in phytochemicals known to significantly affect human health. Cytotoxic, antiviral and antimicrobial activities of different plant extracts were studied and significant results were obtained. Key words:Sorghumvirgatum(Hack); antiviral, cytotoxicity and antimicrobial activities.